Long-cycling multi-polymer coated lithium battery separator and method of making the same

CN117559079BActive Publication Date: 2026-10-20JIANGSU HORIZON NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311745927.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-10-20
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

电池不耐用、电池成本高、充电慢、耗电快,费用高、折损快等问题,无疑是浇灭人们对新能源电动汽车购买欲的一盆盆冷水

Benefits of technology

[0023]本发明提供的长循环多聚合物涂覆锂电池隔膜,在涂覆浆料中引入两种或两种以上聚合物,通过调节两种聚合物的添加比例,将涂覆浆料浊度调节至合适范围,使得涂覆浆料中的聚合物存在微观相分离。浆料涂覆在聚烯烃隔膜上进行水洗相分离时,浆料中的溶剂会与水洗槽中的水进行置换聚合物成膜,与此同时聚合物之间也发生相分离,其中的耐热聚合物PEI会形成球状物分布于涂层中,部分球状物(粒径0.2-0.6μm)分布于涂层的孔中,起到支撑孔,防止循环过程中堵孔问题的发生,从而助力长循环锂电池的发展。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117559079B_ABST
    Figure CN117559079B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of battery separator membranes, in particular to a long-cycle multi-polymer coated lithium battery separator membrane and a preparation method thereof. The long-cycle multi-polymer coated lithium battery separator membrane provided by the application introduces two or two or more polymers in a coating slurry, adjusts the adding proportion of the two polymers, adjusts the turbidity of the coating slurry to a proper range, and makes the polymers in the coating slurry exist in micro-phase separation. When the slurry is coated on a polyolefin separator membrane and washed with water to perform phase separation, the solvent in the slurry will be replaced by water in a water washing tank to form a polymer film, and at the same time, phase separation occurs between the polymers, the heat-resistant polymer PEI in the polymers forms spherical objects and is distributed in the coating, part of the spherical objects is distributed in the holes of the coating, supports the holes, prevents the hole blocking problem from occurring in the circulation process, and thus helps the development of long-cycle lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery separator technology, specifically to a long-cycle polymer-coated lithium battery separator and its preparation method. Background Technology

[0002] Since the advent of electric vehicles, discussions about them have been frequent. As the core component of an electric vehicle, the battery is naturally at the forefront of these discussions. Issues such as short battery life, high battery cost, slow charging, rapid power consumption, high expenses, and rapid deterioration have undoubtedly dampened people's enthusiasm for purchasing new energy electric vehicles. Improving battery cycle life can effectively increase the residual value of electric vehicles and reduce the total lifecycle investment cost of battery swapping stations, playing a crucial role in promoting the popularization of electric vehicles. It also removes technical obstacles to the construction of large-scale energy storage power stations.

[0003] Therefore, the successful preparation of a long-cycle polymer-coated lithium battery separator that is stable and not prone to pore blockage during cycling will help promote the development of long-cycle lithium batteries. Summary of the Invention

[0004] The purpose of this invention is to provide a long-cycle polymer-coated lithium battery separator and its preparation method, so as to solve the problems mentioned in the background art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: 1. A method for preparing a long-cycle polymer-coated lithium battery separator, characterized by comprising the following steps:

[0006] S1. Fluorocarbon resin is added to an organic solvent in one step and stirred at 400-500 rpm at room temperature to dissolve it, thereby preparing a mixture A with a solid content of 3-10 wt%.

[0007] S2. Add the heat-resistant polymer to an organic solvent, heat in a water bath at 70°C, and stir at a rate of 400-500 rpm to dissolve, thereby preparing a mixture B with a solid content of 3-10 wt%.

[0008] S3. Add mixture A to mixture B, stir at 400-500 rpm for 10-20 min, test the mixture solution, and when the turbidity of the mixture solution reaches 50-1000 NTU, prepare mixture solution C, filter to remove iron, and obtain long-cycle polymer coating slurry;

[0009] S4. After the long-cycle polymer coating slurry is coated onto both sides of the polymer base film by roller coating, the surface is washed with water to separate the phases, and then the film is baked and dried and wound up to obtain a long-cycle polymer coated lithium battery separator.

[0010] Furthermore, in step S1, the fluorocarbon resin is any one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, etc.

[0011] Furthermore, in step S2, the heat-resistant polymer is any one or more of polyetherimide, polyimide, polyamideimide, and sodium polystyrene sulfonate.

[0012] Furthermore, the organic solvent is any one or more of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide.

[0013] Furthermore, in step S3, the method for detecting the turbidity of the solution is as follows:

[0014] After preheating the turbidimeter for 20-40 minutes, add the mixed solution dropwise to a clean sample bottle at a temperature of 5-35℃ and a humidity of 75-85% for turbidity detection until the turbidity of the solution reaches 50-1000 NTU.

[0015] During the turbidimeter test, the support surface on which it is placed must be stable and free from vibration. Avoid contact with high temperatures and keep it away from high-intensity magnetic fields, electric fields, and electrical equipment that generates high-frequency waves.

[0016] Furthermore, the sample bottle must be cleaned with water of zero turbidity, both inside and outside, and the outer surface of the bottle must be dried with lens paper; the water sample to be tested must be shaken well and used to clean the sample bottle; after the sample to be tested is put into the sample bottle, the cap must be tightened and the outer surface of the bottle must be dried with lens paper.

[0017] Furthermore, in step S3, the solid content of mixture A and mixture B is the same.

[0018] Furthermore, in step S4, during baking and drying, the drying temperature is 70-75℃ and the drying time is 15-20s.

[0019] Furthermore, the polymer base film is any type of polyolefin film.

[0020] Furthermore, the thickness of the polymer base film is 8-10 μm; the thickness of the long-cycle polymer coating layer is 0.8-1.5 μm.

[0021] A long-cycle polymer-coated lithium battery separator is prepared using the above-described preparation method.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The long-cycle multi-polymer coated lithium battery separator provided by this invention introduces two or more polymers into the coating slurry. By adjusting the addition ratio of the two polymers, the turbidity of the coating slurry is adjusted to a suitable range, resulting in microscopic phase separation of the polymers in the coating slurry. When the slurry is coated on a polyolefin separator and subjected to water washing for phase separation, the solvent in the slurry will replace the water in the washing tank to form a polymer film. At the same time, phase separation also occurs between the polymers. The heat-resistant polymer PEI will form spherical particles distributed in the coating. Some of these spherical particles (particle size 0.2-0.6 μm) are distributed in the pores of the coating, supporting the pores and preventing pore blockage during cycling, thereby contributing to the development of long-cycle lithium batteries. Attached Figure Description

[0024] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:

[0025] Figure 1 This is a microscopic morphology image of the spherical objects in the long-cycle polymer-coated lithium battery separator coating prepared according to the present invention. Detailed Implementation

[0026] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0027] Example 1. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0028] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 3 wt%.

[0029] S2. Mix polyetherimide with N-methylpyrrolidone, heat to 70°C, and stir at 450 rpm to dissolve, to prepare a mixture B with a solid content of 3 wt%.

[0030] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 50-300 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0031] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0032] Example 2. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0033] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 5 wt%.

[0034] S2. Mix polyetherimide with N-methylpyrrolidone, heat to 70°C, and stir at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 5 wt%.

[0035] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 300-600 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0036] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0037] Example 3. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0038] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 8 wt%.

[0039] S2. Polyetherimide and N-methylpyrrolidone are mixed, heated to 70°C, and stirred at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 8 wt%.

[0040] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 600-1000 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0041] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0042] Example 4. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0043] S1. Polyvinylidene fluoride-hexafluoropropylene copolymer was mixed with N-methylpyrrolidone and stirred at 450 rpm at room temperature to dissolve it, thus preparing a mixture A with a solid content of 5 wt%.

[0044] S2. Mix polyetherimide with N-methylpyrrolidone, heat to 70°C, and stir at 450 rpm to dissolve, to prepare a mixture B with a solid content of 3 wt%.

[0045] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 50-300 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0046] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0047] Example 5. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0048] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 8 wt%.

[0049] S2. Polyimide and N-methylpyrrolidone are mixed, heated to 70°C, and stirred at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 4 wt%.

[0050] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 300-600 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0051] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0052] Example 6. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0053] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 5 wt%.

[0054] S2. Polyamide imide and N-methylpyrrolidone are mixed, heated to 70°C, and stirred at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 8 wt%.

[0055] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 600-1000 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0056] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0057] Example 7. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0058] S1. Polyvinylidene fluoride-hexafluoropropylene copolymer was mixed with N-methylpyrrolidone and stirred at 450 rpm at room temperature to dissolve it, thus preparing a mixture A with a solid content of 3 wt%.

[0059] S2. Sodium polystyrene sulfonate and N-methylpyrrolidone were mixed, heated to 70°C, and stirred at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 6 wt%.

[0060] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 50-300 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0061] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0062] Comparative Example 1. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0063] S1. Fluorocarbon resin is mixed with an organic solvent and stirred at 450 rpm at room temperature to dissolve it, thus preparing a mixture A with a solid content of 3 wt%.

[0064] S2. Filter the mixture A to remove iron, and obtain a long-cycle polymer coating slurry;

[0065] S3. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0066] Comparative Example 2. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0067] S1. The heat-resistant polymer is mixed with an organic solvent and stirred at 450 rpm at 70°C to dissolve it, thus preparing a mixture B with a solid content of 3 wt%.

[0068] S2. Filter the mixture B to remove iron, and obtain a long-cycle polymer coating slurry;

[0069] S3. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0070] Comparative Example 3. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0071] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 8 wt%.

[0072] S2. Polyetherimide and N-methylpyrrolidone are mixed, heated to 70°C, and stirred at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 8 wt%.

[0073] S3. Add mixture A dropwise to mixture B and mix thoroughly. After preheating the turbidimeter for 30 minutes, add the mixed solution to the sample bottle for turbidity detection at a temperature of 20℃ and a humidity of 85%. After confirming that the turbidity of the solution reaches 0-50 NTU, the mixed solution C is obtained. Filter to remove iron and obtain long-cycle multi-polymer coating slurry.

[0074] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0075] Comparative Example 4. A method for preparing a long-cycle polymer-coated lithium battery separator, comprising the following steps:

[0076] S1. Polyvinylidene fluoride and N-methylpyrrolidone were mixed and dissolved by stirring at 450 rpm at room temperature to prepare a mixture A with a solid content of 8 wt%.

[0077] S2. Polyetherimide and N-methylpyrrolidone are mixed, heated to 70°C, and stirred at 450 rpm to dissolve, thus preparing a mixture B with a solid content of 8 wt%.

[0078] S3. Mix mixture A and mixture B with the same solid content. After preheating the turbidimeter for 30 minutes, add the mixed solution dropwise to the sample bottle at a temperature of 20°C and a humidity of 85% for turbidity detection until the turbidity of the solution reaches 1000-1500 NTU to obtain mixed solution C. Filter to remove iron to obtain long-cycle multipolymer coating slurry.

[0079] S4. The long-cycle polymer coating slurry is coated onto both sides of a 9μm thick polyolefin-based membrane by roller coating. The surface is then washed with water to separate the phases. The membrane is then baked and dried at 70℃ for 15s. After baking and drying, a 1μm thick long-cycle polymer coating layer is formed on both sides of the polyolefin-based membrane. The membrane is then wound up to obtain a long-cycle polymer-coated lithium battery separator.

[0080] The long-cycle polymer-coated lithium battery separators prepared in Examples 1-3 and Comparative Examples 1-4 were assembled to prepare batteries, and the preparation steps are as follows:

[0081] A. Using LiFePO4 as the positive electrode active material; by weight, 8 parts LiFePO4, 1 part conductive agent SuperP and 1 part binder PVDF are mixed and dispersed in NMP. After mixing with magnetic stirring at room temperature for 12 hours, the resulting slurry is coated on the surface of aluminum foil and dried in a vacuum oven at 80°C for 12 hours to remove residual solvent. The electrode is then taken out, punched into a disc with a diameter of 12 mm, weighed and placed in a glove box for later use.

[0082] B. The glove box is filled with an argon atmosphere, and the water oxygen content is strictly controlled below 0.5ppm. The prepared electrode is placed in the negative electrode shell, 40μL of electrolyte is added, then the separator is placed in with tweezers, another 40μL of electrolyte is added, and finally the lithium sheet and nickel foam are placed in sequence. The positive electrode shell is then closed and sealed with a button cell electric sealing machine. The assembled battery is left to stand for 12 hours before relevant electrochemical tests are performed.

[0083] The tests were conducted on the Wuhan Landian testing system, with a charge / discharge voltage range of 2.4-4.2V and a current density of 0.2C (1C = 1675mAh·g⁻¹). The test results are shown in the table below:

[0084]

[0085] As can be seen from the test results of the examples and comparative examples, the overall performance of the battery assembled using the long-cycle multi-polymer coated lithium battery separator is significantly better than that of the battery assembled using the ordinary single polymer coated separator, that is, the long-cycle multi-polymer coated lithium battery separator has better performance.

[0086] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0087] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a long-cycle polymer-coated lithium battery separator, characterized in that, Includes the following steps: S1. Fluorocarbon resin is added to an organic solvent in one step and stirred at 400-500 rpm at room temperature to dissolve it, thereby preparing a mixture A with a solid content of 3-10 wt%. S2. Add the heat-resistant polymer to an organic solvent, heat in a water bath at 70°C, and stir at a rate of 400-500 rpm to dissolve, thereby preparing a mixture B with a solid content of 3-10 wt%. S3. Add mixture A to mixture B, stir at 400-500 rpm for 10-20 min, test the mixture, and adjust the turbidity of the mixture to 50-1000 NTU by adjusting the addition ratio of fluorocarbon resin and heat-resistant polymer to prepare mixture C. Filter to remove iron to obtain long-cycle multi-polymer coating slurry. S4. After the long-cycle polymer coating slurry is coated on both sides of the polymer base film by roller coating, the surface is washed with water to separate the phase, the film is baked and dried, and then wound up to obtain the long-cycle polymer coated lithium battery separator. In step S2, the heat-resistant polymer is any one or more of polyetherimide, polyimide, polyamideimide, and sodium polystyrene sulfonate; In step S3, the solution turbidity detection method is as follows: after preheating the turbidity meter for 20-40 minutes, in an environment with a temperature of 5-35℃ and a humidity of 75-85%, the mixed solution is added dropwise to a clean sample bottle for turbidity detection until the solution turbidity reaches 50-1000 NTU.

2. The method for preparing a long-cycle polymer-coated lithium battery separator according to claim 1, characterized in that: In step S1, the fluorocarbon resin is any one or more of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene copolymer.

3. The method for preparing a long-cycle polymer-coated lithium battery separator according to claim 1, characterized in that: The organic solvent is any one or more of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide.

4. The method for preparing a long-cycle polymer-coated lithium battery separator according to claim 1, characterized in that: In step S3, the solid content of mixture A and mixture B is the same.

5. The method for preparing a long-cycle polymer-coated lithium battery separator according to claim 1, characterized in that: In step S4, the drying temperature is 70-75℃ and the drying time is 15-20s.

6. The method for preparing a long-cycle polymer-coated lithium battery separator according to claim 1, characterized in that: The polymer base film is any type of polyolefin film.

7. The method for preparing a long-cycle polymer-coated lithium battery separator according to claim 1, characterized in that: The thickness of the polymer base film is 8-10 μm; the thickness of the long-cycle polymer coating layer is 0.8-1.5 μm.

8. A long-cycle polymer-coated lithium battery separator, characterized in that: The long-cycle polymer-coated lithium battery separator is prepared using the preparation method described in any one of claims 1-7.

Citation Information

Patent Citations

  • Polymer mixed slurry coated diaphragm and preparation method thereof

    CN113540687A

  • Carbon nanowire composite material coated lithium ion battery diaphragm and preparation method thereof

    CN116190922A